Implementation of Digital Literacy as a Strategy to Prevent Technological Disparity and Cybercrime in Adolescents: A Case Study at SMKS PGRI Selaawi Garut - Oktavia Oktavia; Feri Alpiyasin; Egi E Saputra; Wisnu Paujan; Roy Kurniawan; Fauzan Syahrul Ramadhan; Retno Ayu Maharani; Anggita Nurul Fadilah; Wilasih Jabarila; Euis Zakiyah; Nova Suci Safitri (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
The community service team, comprising academics and students, conducted activities to investigate the execution of a digital literacy program as a means to mitigate the technological gap and counter the increasing prevalence of cybercrime among adolescents.  The community service at SMKS PGRI Selaawi Garut implemented an educational framework based on four pillars of digital literacy: digital skills, digital ethics, digital security, and digital culture.  Data reveals that 99.2% of Indonesian adolescents are online, although their comprehension of cybersecurity is inadequate.  The curriculum effectively enhanced students' understanding of cybercrime dangers and personal data protection measures through engaging presentations, live simulations, and practical applications.  The findings indicated significant enthusiasm among participants and an enhancement in their practical comprehension of safe and responsible technology utilization.  This program fosters a healthy digital culture and mitigates the risk of technological exploitation among young people.